Percutaneous closure of left ventricular pseudoaneurysm - Yuan, Shi-Min (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2022)
The aim of the present study is to describe the indications, treatment effects, and patient outcomes of percutaneous management of left ventricular pseudoaneurysm (LVPA). The study materials were based on comprehensive literature retrieval since 2004. The mechanisms of LVPA formation can be divided into surgical, percutaneous, and medial disease related. Of the surgical mechanisms, coronary artery bypass grafting prevailed. The formation time was the longest in medical disease-related LVPAs up to 44.4 months. The percutaneous procedures succeeded on the first try in 79 (84.9%) patients, whereas failures were encountered during the percutaneous manoeuvres in 14 (15.1%) patients. Percutaneous closure of LVPA was especially indicated for patients carrying a high surgical risk. The iatrogenic traumas, such as left ventricular venting, should be avoided to prevent this complication. The preliminary cut-off valves of oversize 3.3 mm and oversize ratio 1.6 should be followed for reference for device choice.